Legal Analysis of Legal Protection for Children Born Outside of Marriage According to the Civil Code, Law No. 1 of 1974 concerning Marriage, and Law No. 35 of 2014 concerning Child Protection - Siti Nurjannah Lase; Nada Adista Rambe; Nazwa Ghea Moelanda; Hadi Rafli Maulana Siregar; Layla Hasfajira Br. Tambunan (Jurnal Sahabat ISNU SU, 2025)
Legal protection for illegitimate children in Indonesia is a crucial issue that remains a frequent focus in family law studies. Children born outside of marriage, often referred to as illegitimate children, often face significant legal challenges related to their legal status, inheritance rights, and protection of their well-being. This study aims to analyze the legal protection of illegitimate children from a civil law perspective in Indonesia. Illegitimate children often face discrimination and injustice, both in terms of legal status, inheritance rights, and other protections that every child should receive. This study uses a normative juridical approach by examining various applicable laws and regulations, such as the Civil Code (KUHPerdata), Law No. 1 of 1974 concerning Marriage, and Law No. 35 of 2014 concerning Child Protection, as amended. The analysis found that although civil law provides protection for illegitimate children, there are loopholes that allow for injustice to these children, particularly in terms of recognizing child status, inheritance rights, and regulating relationships with biological parents. This study suggests the need for legal reform to provide better protection and ensure that the rights of children born out of wedlock can be accommodated more fairly in accordance with the principles of human rights protection and child welfare.